REVIEW : ANALISIS PENGGUNAAN ANTIBIOTIK PROFILAKSIS PADA PASIEN PASCA BEDAH SESAR DI BEBERAPA RUMAH SAKIT DI INDONESIA - Shalsabina, Vina; Hermanto, Faizal (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Caesarean section shows an increase from year to year. The number of cesarean births every year also has an impact on the increase in post-surgical complications. The purpose of this article is to examine the effectiveness of the use of prophylactic antibiotics in patients after caesarean section. A systematic review of articles and publications published in the year 2014 to 2024 used 9 articles and used the search keyword, which is prophylactic antibiotics after caesarean section. The description of the use of prophylactic antibiotics that was seen includes the type, time of administration, method of administration, duration of treatment and dose of antibiotics, compared to the main guidelines of basic treatment of pharmacology and therapy according to Goodman & Gilman. It can be concluded that the most widely used antibiotics are the third generation cephalosporins, namely ceftriaxone and cefotaxime. These antibiotics are broad-spectrum, and target gram positive and gram negative bacteria, and are commonly used as prophylactic antibiotics in caesarean section patients.